Ensino de História e patrimônio cultural: Estratégia de aprendizagem histórica na cidade de Conceição do Araguaia - PA - Carvalho, Martha Melo (Universidade Federal do Tocantins, 2022)
In order to analyze cultural heritage as a strategy for teaching local History in basic education we conducted a participatory research with a group of 1st year’s High School students at Crescer School, located in Conceição do Araguaia, Amazon Region of Brazil. The mobilization and sensitization of students was carried out based on methodologies and tools already existing at the Brazilian National Historical and Artistic Heritage Institute (IPHAN). The intervention aimed to identify, describe, classify, define and recognize the material available locally, specifically the material by the Dominican priests, the Santa Rosa School and the Main Catholic Church (Nossa Senhora da Conceição). As theoretical fundament about teachinglearning of History, we adopted the concepts of Paulo Freire (1996), Sandra C. A. Pelegrini (2006), Rüsen (2010) and Ricardo de Aguiar Pacheco (2017). Regarding reflections on education by heritance, we used guidelines of manuals produced by IPHAN. As a result, we created a didactic and inedited website (https://sites.google.com/ view/edupatrimonialmarthamelo/ inicio) to encourage and strengthen educational practices in History Teaching around Cultural Heritage and Local History, promoting identification of students with local references.